Effects of the Two-Dimensional Structure of Trust on Patient Adherence to Medication and Non-pharmaceutical Treatment: A Cross-Sectional Study of Rural Patients With Essential Hypertension in China - Feng, Yingchao; Guan, Shuai; Xu, Yanyun; Chen, Wenqin; Huang, Xianhong; Wang, Xiaohe; Zhang, Meng (Frontiers in Public Health, 2022)
In rural China, treatment adherence of patients with hypertension remains a challenge. Although early research on patient adherence has confirmed the importance of trust in doctors, the relative contribution and influence of the two-dimensional structure of trust on adherence has not been explored. Thus, this study examined the effects of patient trust in primary care physicians’ (PCPs) benevolence and ability on medication adherence, dietary management, and physical activity. The data were derived from 2,533 patients at 54 primary health institutions in China (village level) from February 2017 to May 2018. Participants were assessed using the Chinese version of the Wake Forest Physician Trust Scale and the Therapeutic Adherence Subscale for Hypertensive Patients. Other information included region, gender, age, and self-rated health status. The results of multiple linear regression and structural equation modeling confirmed that patient trust in PCPs’ benevolence was positively correlated with patient adherence to medication, diet management, and physical activity. Patient trust in PCPs’ ability was negatively correlated with adherence to dietary management and physical activity. We concluded that interventions aimed at increasing PCP benevolence have the greatest potential to improve patient adherence to hypertension treatment. Under the country’s policy of advocating to improve PCPs’ diagnoses and treatment technology, it may be important to cultivate doctors’ communication skills, medical ethics, and other benevolent qualities to improve patients’ adherence with drug and non-drug treatments.